Photocuring dental resin adhesive containing silane coupling agent modified monomer as well as preparation and application of photocuring dental resin adhesive
The light-cured dental resin adhesive modified with silane coupling agent solves the problems of insufficient bonding strength, durability and hydrolysis resistance of enamel adhesives, and achieves stable bonding of enamel and restorations, which is suitable for a variety of clinical applications.
Patent Information
- Application Number
- CN202511271756.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2025-12-12
AI Technical Summary
Existing enamel adhesives are inadequate in terms of bond strength, durability, and hydrolysis resistance. In particular, they are prone to microleakage and material degradation at the bond interface when used in humid environments, making it difficult to meet the unique requirements of enamel bonding.
A light-cured dental resin adhesive using a monomer modified with a silane coupling agent is used. The isocyanate reacts with the hydroxyl groups on the dimethacrylate resin monomer to generate a silane-modified grafted resin monomer, forming a covalent cross-linked network that chemically bonds with the enamel and restoration surface, thereby enhancing the interfacial bonding strength.
It improves the bonding strength and stability between tooth enamel and restoration, avoids phase separation problems, enhances the hydrolysis resistance and long-term stability of the adhesive in humid environments, and is suitable for a variety of clinical scenarios.
Smart Images

Figure CN121102022A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dental restorative materials and their preparation and application, specifically relating to a light-cured dental resin adhesive containing a silane coupling agent-modified monomer and its preparation and application. Background Technology
[0002] Dental resin adhesives are a key component of modern dental restorative materials, widely used in cavity restorations, veneers, crowns and bridges, indirect restorations, and orthodontic attachments. Their primary function is to achieve a strong bond between the restorative material and the tooth structure, thereby ensuring the stability and lifespan of the restoration.
[0003] Depending on the application, light-cured dental resin adhesives are divided into dentin adhesives and enamel adhesives. Dentin is mainly composed of 70% inorganic minerals, 20% organic components, and about 10% water, and contains dentinal tubules. Currently, clinically used dentin adhesives primarily work by using hydrophilic adhesives to penetrate the collagen fiber network within the dentinal tubules, forming micromechanical interlocks for bonding. After curing, it becomes hydrophobic. This bonding method requires maintaining a moist environment in the dentin after acid etching to prevent collagen network collapse, and also requires good permeability and sealing properties to prevent postoperative sensitivity and microleakage. Unlike dentin, enamel is a highly mineralized structure containing approximately 96% inorganic components and has a dense structure. Currently, clinically used enamel adhesives primarily work by penetrating the roughened surface created by phosphoric acid etching and demineralization, forming micromechanical interlocks after curing for bonding. Therefore, to achieve long-term stable bonding between tooth enamel and indirect restorations (crowns, bridges, inlays, veneers, etc.), there are actually different requirements for enamel adhesives and dentin adhesives.
[0004] Although nearly 20 approved dental adhesives can be found on the website of the National Medical Products Administration, most of them state in their scope of application and intended use that they can be used for bonding enamel and dentin to resin, metal, and ceramic restorations, and have already been used clinically. However, the formulation design of these adhesives does not fully consider the differences between dentin and enamel bonding. The commonly used dimethicone resin monomers lack targeted design, which makes the bonding strength and durability of enamel bonding restorations still challenging. First, enamel has a dense structure and lacks a collagen fiber network. It relies solely on the micro-roughened surface exposed after acid etching and demineralization to form a bonding interface with different materials (such as ceramics and metals) through micro-locking. Therefore, unlike the wet bonding operation of dentin, enamel must be thoroughly rinsed and kept dry after acid etching. Not only will residual moisture affect the bonding effect, but the lack of affinity between the adhesive monomers and minerals will also affect the penetration of the adhesive and reduce the bonding strength. Secondly, because tooth enamel is constantly exposed to the moist environment of the oral cavity, the requirements for the hydrolysis resistance and aging resistance of adhesives are higher. Some dimethicone resin monomers with hydrophilic hydroxyl groups, such as bisphenol A glycerol dimethicone (BisGMA), may cause the adhesive to absorb water and hydrolyze to a certain extent over time. This can lead to reduced bonding strength at the bonding interface due to microleakage or material degradation, resulting in restoration detachment or secondary caries. Thirdly, enamel bonding is highly dependent on the integrity of the enamel. For severely demineralized or worn enamel, the rough morphology after acid etching is atypical, resulting in poor bonding performance. Bonding to marginal areas or atypical enamel structures (such as the incisal edge and cervical region) is even more difficult. This places higher demands on the permeability of enamel adhesives to the bonding surface, their affinity for inorganic minerals, their hydrolysis resistance, and their aging resistance.
[0005] Therefore, it is necessary to develop a novel light-cured enamel resin adhesive suitable for various clinical scenarios, taking into account the unique characteristics of enamel bonding, in order to meet the high-performance requirements of modern dental restoration. Summary of the Invention
[0006] The technical problem to be solved by this invention is to provide a novel light-cured enamel resin adhesive suitable for various clinical scenarios, and to provide a light-cured dental resin adhesive containing a silane coupling agent-modified monomer and its preparation method. This method utilizes the advantage of silane coupling agents in enhancing interfacial adhesion. An isocyanate-containing silane coupling agent is selected, and its isocyanate reacts with the hydroxyl groups on the dimethacrylate resin monomer to generate a silane-modified grafted resin monomer. The resulting dental resin adhesive can not only enhance its mechanical properties by forming a covalent cross-linked network through photo-induced monomer polymerization, but also utilize the grafted silane coupling agent to form a chemical bond with the bonded substrate (enamel, indirect restoration), thereby improving the interfacial bonding strength and achieving long-term stable adhesive restoration.
[0007] The present invention provides a photocurable dental resin adhesive containing a silane coupling agent-modified monomer, comprising a resin matrix, an organic polymer, and a photoinitiator.
[0008] The resin monomer is composed of a main resin and a diluent resin in a mass ratio of (6-8):(4-2), and the resin matrix accounts for 88-99% of the total mass of the dental resin adhesive.
[0009] The main resin is one, two, or three of the following: bisphenol A glycidyl methacrylate (BisGMA), silane-modified bisphenol A glycidyl methacrylate (Si-BisGMA), and urethane dimethacrylate (UDMA).
[0010] The main resin matrix comprises Si-BisGMA and BisGMA in a mass ratio of (25-75):(75-25).
[0011] Preferably, the main resin matrix comprises Si-BisGMA and BisGMA in a mass ratio of 1:1.
[0012] The diluting resin is one or more of the following: hydroxyethyl methacrylate (HEMA), triethylene glycol dimethacrylate (TEGDMA), 1,6-hexanediol dimethacrylate (HDDMA), 2-hydroxypropyl methacrylamide (HPMA), and methyl methacrylate (MMA).
[0013] Preferably, the diluted resin matrix comprises TEGDMA and HDDMA in a mass ratio of 2:1.
[0014] The organic polymer is polymethyl methacrylate (PMMA) with a molecular weight of 10,000-35,000, and its addition amount accounts for 0-10% of the total mass of the dental resin adhesive.
[0015] The photoinitiator is composed of a main initiator and a co-initiator in a mass ratio of 1:1-2. The main initiator is camphorquinone (CQ), and the co-initiator is dimethyl ethyl methacrylate (DMAEMA) and diphenyliodonium hexafluorophosphate (DPIHP), with a mass ratio of DMAEMA to DPIHP of 1:0.5-2.
[0016] This invention also provides a light-cured dental resin adhesive containing a silane coupling agent-modified monomer and its preparation and application methods, comprising:
[0017] (1) Dissolve BisGMA in dichloromethane to prepare a solution, and dissolve 3-isocyanate-propyltrimethoxysilane IPTMS in dichloromethane to prepare a silane coupling agent solution. Add dibutyltin dilaurate to the BisGMA solution and then add the silane coupling agent solution dropwise. React at room temperature for 24-72 hours. After the reaction is completed, collect the silane-modified resin monomer Si-BisGMA by rotary evaporation and dry it in the dark for later use.
[0018] (2) Dissolve PMMA in acetone to prepare a solution, and then add all other resin matrices and photoinitiators that do not contain Si-BisGMA obtained in step (1) to the solution and mix them evenly for later use.
[0019] (3) The Si-BisGMA obtained in step (1) and the resin mixture prepared in step (2) are mixed evenly in different proportions to obtain a light-cured dental resin adhesive containing a silane coupling agent modified monomer.
[0020] The dental resin adhesive of the present invention, which contains a silane coupling agent-modified monomer and has a photo / chemical dual curing method, can achieve stable bonding to tooth enamel and dental restorative materials of different materials (metal, ceramic, resin-based composite materials). Beneficial effects
[0021] 1. This invention prepares Si-BisGMA by covalently grafting a silane coupling agent with a light-cured methacrylate resin monomer through a chemical reaction between isocyanate and hydroxyl groups. This Si-BisGMA can not only undergo photo-initiated free radical reactions with other light-cured resin monomers in dental adhesives, but also react with the hydroxyl groups on these monomers via the siloxane bonds of the silane coupling agent, increasing internal cross-linking density and enhancing the cohesive energy of the bonding interface. Furthermore, it can react with polar groups present on the enamel surface and on metal, resin, and ceramic restorations, resulting in chemical cross-linking. Si-BisGMA physically penetrates into the gaps between enamel prisms and the restoration surface, bonding through physical micro-locking. Simultaneously, the retained siloxane bonds react with the enamel, restoration, and the interior of the adhesive, enhancing the bonding strength between the dental resin adhesive and hard dental tissues, metal, resin, or ceramic restorations at the bonding interface, thus improving the compatibility and long-term stability of the bonding interface.
[0022] 2. Compared with the method of directly adding silane coupling agents to dental adhesives to improve bonding performance, the dental adhesives of this invention, which incorporate silane-modified resin monomers, can effectively avoid phase separation problems that are prone to occur in two-phase or multi-phase blend systems, can circumvent the adverse effects of silane coupling agent hydrolysis, and have the ability to adjust the polarity and non-polarity of resin monomers, thereby ensuring good dispersibility of silane coupling agent components in dental resin adhesive systems and their long-term strengthening effect on the bonding interface.
[0023] 3. This invention prepares Si-BisGMA by reacting the isocyanate group of 3-isocyanate-propyltrimethoxysilane with the hydroxyl group in the BisGMA molecule. However, based on its reaction principle, the resin monomer can be extended to other methacrylate monomers with hydroxyl side groups, such as hydroxyethyl methacrylate (HEMA) and 2-hydroxypropyl methacrylamide (HPMA), to prepare more silane coupling agent modified resin monomers such as Si-HEMA and Si-HPMA. By changing the resin monomer and controlling the grafting degree of the silane coupling agent, the mechanical properties, flowability, viscosity, and polymerization rate of dental adhesives can be more specifically adjusted, providing more flexible formulation design methods for diverse needs in clinical applications. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the reaction for preparing Si-BisGMA in Example 1 of the present invention;
[0025] Figure 2 The hydrogen nuclear magnetic resonance spectrum of the Si-BisGMA prepared in Example 1 of this invention;
[0026] Figure 3 The Fourier transform infrared spectrum of the Si-BisGMA prepared in Example 1 of this invention;
[0027] Figure 4 The degree of silane grafting of Si-BisGMA prepared in Examples 1-3 of this invention;
[0028] Figure 5 The immediate flexural strength of the dental resin adhesives obtained in Examples 4-6 of this invention;
[0029] Figure 6 The immediate flexural modulus of the dental resin adhesives obtained in Examples 4-6 of this invention;
[0030] Figure 7 The immediate shear bond strength of the dental resin adhesive obtained in Examples 4-6 of the present invention to orthodontic metal brackets in the enamel.
[0031] Figure 8 The immediate shear bond strength of the dental resin adhesive obtained in Examples 4-6 of this invention to the composite resin in tooth enamel.
[0032] Figure 9 The immediate shear bond strength of the dental resin adhesive obtained in Examples 4-6 of the present invention to dental lithium disilicate glass ceramics in tooth enamel.
[0033] Figure 10 The dental resin adhesive obtained in Examples 4-6 of this invention has a one-month aging shear bond strength to orthodontic metal brackets in tooth enamel.
[0034] Figure 11 The dental resin adhesive obtained in Examples 4-6 of this invention exhibits one-month aging shear bond strength of composite resin in tooth enamel.
[0035] Figure 12 The dental resin adhesive obtained in Examples 4-6 of this invention has a one-month aging shear bond strength of dental lithium disilicate glass ceramic in tooth enamel.
[0036] Figure 13 Cell compatibility characterization of the dental resin adhesives obtained in Examples 4-6 of this invention. Detailed Implementation
[0037] The present invention can be better understood from the following embodiments. However, the following specific embodiments are merely illustrative of the present invention and are not intended to limit the invention. The present invention is illustrated by the synthesis of Si-BisGMA and the preparation of its dental resin adhesive, but the reaction principle of 3-isocyanate-propyltrimethoxysilane IPTMS with other methacrylate monomers with hydroxyl side groups is similar. Those skilled in the art can make modifications to the following embodiments as needed after reading this specification, but modifications that are within the scope of the specification and claims of the present invention do not have significant innovation.
[0038] Performance evaluation:
[0039] (1) Adhesive properties
[0040] Fresh, caries-free, and unrepaired bovine mandibular incisors were selected. To ensure a smooth bonding surface, the tooth was embedded and polished with dental self-curing resin to expose the enamel. The tooth surface should be kept moist during the polishing process to ensure good bonding properties.
[0041] Apply 37% dental phosphoric acid etching agent to the enamel surface using a disposable dental swab. After 15 seconds, rinse the enamel surface with deionized water. After blotting the surface with filter paper, apply the adhesives from Examples 4-6 and Comparative Examples 1-2 to the enamel surface and the bonding surface of the orthodontic metal brackets, respectively. After the adhesives have fully penetrated, bond the metal brackets to the enamel surface. Cure the adhesives by irradiating them with a 10W light-curing machine with a wavelength range of 385nm-515nm for 20 seconds. Test the immediate bond strength after placing the prepared bonded samples in physiological saline at 37°C for 24 hours, and test the aging bond strength after placing them in physiological saline at 37°C for one month.
[0042] Apply 37% dental phosphoric acid etching agent to the enamel surface using a disposable dental swab. After 15 seconds, rinse the enamel surface with deionized water. After blotting the surface with filter paper, apply perforated adhesive tape with 3mm pores to the enamel surface. Apply the adhesives from Examples 4-6 and Comparative Examples 1-2 into the pores. After the adhesives have fully penetrated, irradiate the adhesives with a 10W light curing machine (wavelength range 385nm-515nm) for 20 seconds to cure them. Then, cure the composite resin onto the adhesive surface. Test the immediate bond strength after placing the prepared bonded samples in physiological saline at 37°C for 24 hours, and test the aging bond strength after placing them in physiological saline at 37°C for one month.
[0043] Apply 37% dental phosphoric acid etching agent to the enamel surface using a disposable dental swab. After 15 seconds, rinse the enamel surface with deionized water. After blotting the surface with filter paper, apply the adhesives from Examples 4-6 and Comparative Examples 1-2 to the enamel and glass-ceramic surfaces respectively. After the adhesives have fully penetrated, bond the glass-ceramic to the enamel surface. Cure the adhesive by irradiating it with a 10W light-curing machine with a wavelength range of 385nm-515nm for 20 seconds. Test the immediate bond strength after placing the prepared bonded samples in physiological saline at 37°C for 24 hours, and test the aging bond strength after placing them in physiological saline at 37°C for one month.
[0044] After removing the bonded sample from the saline solution and drying it, it was placed into a shear testing apparatus. The apparatus was placed horizontally between the two parallel platforms of the universal testing machine. The upper parallel platform was set to descend at a rate of 1 mm / min until the bonded sample was destroyed. The shear bond strength was calculated using the following formula: Where τ is the shear strength, P is the maximum applied load, and l is the diameter of the bonding surface.
[0045] (2) Cytotoxicity evaluation
[0046] The prepared adhesive materials from Examples 4-6 and Comparative Examples 1-2 were placed into a mold with a diameter of 12 mm and a height of 2 mm. Both sides were cured by irradiating with a 10W light-curing machine with a wavelength range of 385 nm–515 nm for 20 seconds each. The cured adhesive samples were then removed from the mold. The adhesive samples were immersed in 75% medical alcohol (volume fraction) and irradiated under a UV lamp for 4 hours, with the alcohol replaced every 2 hours. The samples were then washed three times with phosphate-buffered saline (PBS), with 30-minute intervals between each wash. The ratio of cell culture medium to resin sample volume / standard surface area was 1 mL : 1.25 cm². 2 Extracts were prepared for L929 fibroblast culture to assess the biocompatibility of the resin. The prepared cell suspension was added to 96-well plates and incubated in a CO2 incubator (37℃, 5% CO2) for 2 hours until cell attachment was achieved. The cells were then replaced with the extract and co-cultured. Samples were taken on days 1, 4, and 7. The 96-well plates were removed from the incubator, the original culture medium was aspirated, and 200 μL of CCK-8 working solution (prepared by adding 1 mL of CCK-8 to 9 mL of fresh culture medium, freshly prepared) was added to each well. The 96-well plates were returned to the incubator; after 4 hours of incubation, 100 μL of the liquid was aspirated from each well and added to a microplate. The absorbance was measured at 450 nm using a microplate reader. The absorbance of cells incubated in normal cell culture medium on the plates served as the control group (TCP).
[0047] Example 1
[0048] Weigh 5.12 g of BisGMA and dissolve it in 100 mL of dichloromethane that has been dehydrated by distillation. Then weigh 4.32 g of IPTMS and dissolve it in 50 mL of dichloromethane that has been dehydrated by distillation. Add 150 μL of dibutyltin dilaurate catalyst to the dichloromethane solution of BisGMA, and then add dropwise a solution of 3-isocyanatopropyltrimethoxysilane in dichloromethane. After mixing thoroughly, react at room temperature for 72 hours. After the reaction is complete, collect the silane-modified product Si-BisGMA by rotary evaporation.
[0049] Example 2
[0050] The reaction time of Example 1 was changed to 24 hours.
[0051] Example 3
[0052] The reaction time of Example 1 was changed to 48 hours.
[0053] Examples 4-6 and Comparative Examples 1-2
[0054] A formulation for a light-cured dental resin adhesive containing a silane coupling agent-modified monomer is provided, the composition of which is shown in Table 1. The adhesive is prepared according to the following steps: Polymethyl methacrylate (PMMA) is weighed and added to a flask containing 10 mL of acetone, and stirred at room temperature until completely dissolved. TEGDMA, HDDMA, and BisGMA are weighed into a beaker, and the PMMA solution and photoinitiator system (CQ, DMAEMA, and DPIHP) are added. The mixture is mechanically stirred at room temperature until the acetone has completely evaporated, yielding resin paste 1. The silane-modified product Si-BisGMA prepared in Example 1 is mixed thoroughly with resin paste 1 to obtain the dental resin adhesive.
[0055] Table 1. Composition of the light-cured dental resin adhesives in Examples 2-5 and Comparative Examples 3-6
[0056] analyze Figure 1 It can be seen that, Figure 1 The reaction process of the silane-modified product Si-BisGMA described in Example 1 is shown. Si-BisGMA is generated by isocyanate reaction between the hydroxyl groups on BisGMA and the isocyanates on IPTMS to form amide bonds, thereby side-linking IPTMS and giving it the ability to chemically crosslink.
[0057] analyze Figure 2 It can be seen that, Figure 2 The hydrogen nuclear magnetic resonance data of the silane-modified product Si-BisGMA described in Example 1 are shown, and the Si-BisGMA was successfully prepared.
[0058] analyze Figure 3 It can be seen that, Figure 3 The Fourier transform infrared (FTIR) data of BisGMA, IPTMS, and the silane-modified product Si-BisGMA described in Example 1 are shown. The FTIR data of BisGMA shows infrared characteristic peaks of hydroxyl groups and carbon-carbon double bonds, while the FTIR data of IPTMS shows infrared characteristic peaks of isocyanates and methoxysilyl groups. The FTIR data of the silane-modified product Si-BisGMA described in Example 1 does not show infrared characteristic peaks of hydroxyl groups and isocyanates, but shows infrared characteristic peaks of imino groups, methoxysilyl groups, and carbon-carbon double bonds. This proves that Si-BisGMA is obtained by grafting hydroxyl groups on BisGMA with isocyanates on IPTMS, and retains methoxysilyl groups with sol-gel reaction and carbon-carbon double bonds that can participate in photocuring reaction.
[0059] analyze Figure 4 It can be seen that, Figure 4The results show the silane grafting degree of the silane-modified product Si-BisGMA described in Examples 1-3. It can be seen that the silane grafting degree of the silane-modified product Si-BisGMA described in Example 1 is the highest, proving that a reaction time of 72 hours is beneficial to the formation of Si-BisGMA.
[0060] analyze Figure 5 and Figure 6 It can be seen that, Figure 5 and Figure 6 The flexural strength and flexural modulus of the adhesives described in Examples 4-6 and Comparative Examples 1-2 are shown respectively. The flexural strength and flexural modulus of the adhesives described in Examples 4-6 are approximately the same as those of the adhesive described in Comparative Example 1, but greater than those of the adhesive described in Comparative Example 2. This demonstrates that the amount of the silane-modified product Si-BisGMA added in Example 1 should be within a suitable range to improve the flexural properties of the adhesive. This is because Si-BisGMA can, on the one hand, utilize the methoxysilane groups to undergo a sol-gel reaction with the hydroxyl groups inside the adhesive, increasing the chemical crosslinking density; on the other hand, the introduction of long side chains increases the spacing between polymer networks, which will adversely affect the flexural properties of the adhesive.
[0061] Figure 7 , Figure 8 and Figure 9 , Figure 10 , Figure 11 and Figure 12 The immediate shear bond strength and one-month aging shear bond strength of the adhesives described in Comparative Examples 1, 4-6, and 2 with orthodontic metal brackets, composite resin, and lithium disilicate glass ceramics were measured, respectively. The immediate shear bond strength and one-month aging shear bond strength of the adhesives described in Examples 4-6 with orthodontic metal brackets, composite resin, and lithium disilicate glass ceramics were greater than those of the adhesives described in Comparative Examples 1-2. This proves that the amount of silane-modified product Si-BisGMA added in Example 1 should be within a suitable range to improve the shear bond strength of the adhesive. This is because Si-BisGMA can, on the one hand, utilize the methoxysilane groups to react with the hydroxyl groups inside the adhesive to increase the chemical crosslinking density inside the adhesive. At the same time, the methoxysilane groups react with the polar groups on the tooth surface or the surface of the bonded material to jointly improve the shear bond strength. On the other hand, the introduction of long side chains increases the spacing between polymer networks, which will have an adverse effect on the shear bond strength of the adhesive.
[0062] analyze Figure 13 It can be seen that, Figure 13 The cell proliferation capacity of the adhesives described in Comparative Examples 1-2 and Examples 4-6 was shown at 1 day, 4 days, and 7 days, demonstrating that the addition of the silane-modified product Si-BisGMA described in Example 1 had no adverse effect on the biocompatibility of the adhesive.
Claims
1. A light-curing dental resin adhesive containing a silane coupling agent-modified monomer, comprising a resin matrix, an organic polymer, and a photoinitiator, characterized in that, The resin matrix comprises a main resin and a diluent resin. The main resin comprises silane-modified methacrylate resin monomers and unmodified methacrylate resin monomers. The organic polymer is polymethyl methacrylate. The photoinitiator is composed of a main initiator and a co-initiator. Its preparation method includes the following steps: (1) Dissolve the methacrylate resin monomer in dichloromethane to prepare a solution, and at the same time dissolve 3-isocyanate-propyltrimethoxysilane in dichloromethane to prepare a silane coupling agent solution. Add dibutyltin dilaurate to the resin solution and then add the silane coupling agent solution dropwise. React at room temperature for 24-72 hours. After the reaction is completed, collect the silane-modified resin monomer by rotary evaporation and dry it in the dark for later use. (2) Dissolve polymethyl methacrylate in acetone to prepare a solution, and then add all other resin matrices and photoinitiators that do not contain the silane-modified resin monomer obtained in step (1) to the solution and mix them evenly for later use. (3) Mix the silane-modified methacrylate resin monomer obtained in step (1) and the resin mixture prepared in step (2) evenly to obtain a light-cured dental resin adhesive containing a silane coupling agent-modified monomer.
2. The dental resin adhesive according to claim 1, characterized in that, The adhesive composition and ratio are as follows: the mass ratio of main resin: diluent resin: organic polymer: initiator is (59-70):(40-18):(0-10):(1-2).
3. The dental resin adhesive according to claim 1, characterized in that, The main resins are bisphenol A glycidyl methacrylate (BisGMA) and silane-modified bisphenol A glycidyl methacrylate (Si-BisGMA), with a mass ratio of (75-25):(25-75).
4. The dental resin adhesive according to claim 1, characterized in that, The diluent is one or more of the following: hydroxyethyl methacrylate (HEMA), triethylene glycol dimethacrylate (TEGDMA), 1,6-hexanediol dimethacrylate (HDDMA), 2-hydroxypropyl methacrylamide (HPMA), and methyl methacrylate (MMA).
5. The dental resin adhesive according to claim 1, characterized in that, The polymethyl methacrylate (PMMA) organic polymer has a molecular weight range of 10,000-35,000.
6. The dental resin adhesive according to claim 1, characterized in that, The main initiator is camphorquinone (CQ), and the co-initiators are dimethyl ethyl methacrylate (DMAEMA) and diphenyliodonium hexafluorophosphate (DPIHP). The mass ratio of the main initiator to the co-initiator is 1:1-2, and the mass ratio of DMAEMA to DPIHP is 1:0.5-2.
7. The dental resin adhesive of claim 1 is used as an enamel adhesive in the restoration of tooth defects.
Citation Information
Cited By
Oxygen-producing hydrogel for myocardial repair and preparation method thereof
CN122031768A